Least-squares design of digital fractional-order operators - Barbosa, Ramiro (2019)
In this paper we develop a method for obtaining digital rational approximations to fractional-order operators of type s^y, where y e R. The proposed method is based on the least-squares (LS) minimization between the impulse response of the fractional Euler/Tustin operators and the digital rational-fraction approximation. We make a comparison with other approaches and the results reveal that the LS method gives superior approximations. The effectiveness of the method is demonstrated both in the time and frequency domains through an illustrative example.